2021
DOI: 10.1093/europace/euaa377
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning and the electrocardiogram: review of the current state-of-the-art

Abstract: In the recent decade, deep learning, a subset of artificial intelligence and machine learning, has been used to identify patterns in big healthcare datasets for disease phenotyping, event predictions, and complex decision making. Public datasets for electrocardiograms (ECGs) have existed since the 1980s and have been used for very specific tasks in cardiology, such as arrhythmia, ischemia, and cardiomyopathy detection. Recently, private institutions have begun curating large ECG databases that are orders of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
112
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 74 publications
0
112
0
4
Order By: Relevance
“…Therefore this review will not focus upon studies analysing ML application to electrocardiogram (ECG) nor cardiac imaging. The extensive research into electrocardiogram (ECG) signal processing and ECG interpretation has been recently synthesised in the state-of-the-art systematic review of application of deep learning to the ECG [26]. Somani et al (2021) provide an overview of deep learning application to ECGs, its benefits, limitations as well as future areas for improvement [26].…”
Section: Common Hf Problems Addressed By MLmentioning
confidence: 99%
“…Therefore this review will not focus upon studies analysing ML application to electrocardiogram (ECG) nor cardiac imaging. The extensive research into electrocardiogram (ECG) signal processing and ECG interpretation has been recently synthesised in the state-of-the-art systematic review of application of deep learning to the ECG [26]. Somani et al (2021) provide an overview of deep learning application to ECGs, its benefits, limitations as well as future areas for improvement [26].…”
Section: Common Hf Problems Addressed By MLmentioning
confidence: 99%
“…Deep learning (DL) techniques can reduce the workload in decision-making tasks, leading to faster and more consistent decisions while releasing human resources for other tasks. In this sense, increased computational power and the availability of ECG databases with clinical annotations have driven the development of DL techniques for unsupervised ECG analysis (Parvaneh et al, 2019 ; Somani et al, 2021 ). For the detection of AF different DL methodologies have been proposed, including hierarchical attention networks (Mousavi et al, 2020 ), long short-term memory (Faust et al, 2018 ; Andersen et al, 2019 ; Dang et al, 2019 ; Jin et al, 2020 ), convolutional neural network (CNN) (He et al, 2018 ; Xia et al, 2018 ; Lai et al, 2019 ; Huang and Wu, 2020 ; Zhang et al, 2020 ), and approaches combining recurrent neural networks with CNN (Fujita and Cimr, 2019 ; Shi et al, 2020 ; Wang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent breakthroughs in artificial intelligence have demonstrated that much more information may be available from the ECG to diagnose such conditions than currently leveraged 31,32 . Deep learning (DL), a class of machine learning that uses hierarchical networks to extract lower-dimensional features from a higher dimensional data input, has demonstrated significant potential for enabling ECG-based predictions and diagnoses 33 . For example, DL has been used to identify patients with atrial fibrillation while in normal sinus rhythm 34 , predict incident atrial fibrillation 35 , identify patients amenable to cardiac resynchronization therapy 36 , evaluate LV diastolic function 37 , evaluation of patients with echocardiographically concealed long QT syndrome 38 , predict risk of sudden cardiac death 39 , and to predict low LVEF.…”
Section: Introductionmentioning
confidence: 99%